Initial study of electrical capacitance tomography for detecting agarwood - Muhammad Aiqil, Sarudin; Yasmin, Abdul Wahab; Ain Eazriena, Che Man; Nurhafizah, Abu Talip @ Yusof; Rohana, Abdul Karim; Suzanna, Ridzuan Aw; Juliza, Jamaludin; Jaysuman, Puspanathan; Elmy Johana, Mohamed; Ruzairi, Abdul Rahim; Sia, Yee Yu (Malaysian Society for Computed Tomography and Imaging (MyCT), 2023)
This study investigates the use of electrical capacitance tomography (ECT) as a non-invasive method to monitor the quantity of agarwood in a tree. Previous methods like sonic, magnetic inductive, and microwave tomography have been used, but it's unclear if voltage variations in resin regions are significant. The ECT system was developed using COMSOL Multiphysics software, modeling 8 electrodes in a 2-dimensional setup. The electrical potential distribution and performance analysis of the ECT model were evaluated for different agarwood locations, shapes, and sizes. The forward problem was solved using COMSOL, and tomogram images were obtained using a linear back-projection algorithm in MATLAB. The images closely matched the reference image based on the mean structural similarity index (MSSIM) values. This suggests the potential for accurately reconstructing agarwood images using ECT.